2021
DOI: 10.17691/stm2021.13.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton Microscopy and Mass Spectrometry for Revealing Metabolic Heterogeneity of Hepatocytes in vivo

Abstract: The aim of the investigation was to study the possibility of revealing the heterogeneity of normal liver hepatocytes in terms of metabolic status using the modern methods of multiphoton microscopy and mass spectrometry.Materials and Methods. Heterogeneity of hepatocytes in terms of total metabolic activity was assessed using multiphoton microscopy based on the autofluorescence intensity of intracellular cofactors NAD(P)H and FAD. Hepatocyte heterogeneity in terms of intensity of intracellular metabolic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Topographical distributions of liver metabolic processes have been recently re-examined by LCM approaches coupled with RNA sequencing to provide a comprehensive transcriptome analysis of human and mouse liver zonation 40 . In addition, a recent study using MSI has shown hepatocyte heterogeneity in terms of amino acid and lipid composition 69 . Also, using MSI, liver metabolome was shown to change with fasting in a localized pattern, including increased levels of fatty acids and tricarboxylic acid cycle intermediates 70 …”
Section: Spatial Heterogeneity In the Mammalian Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Topographical distributions of liver metabolic processes have been recently re-examined by LCM approaches coupled with RNA sequencing to provide a comprehensive transcriptome analysis of human and mouse liver zonation 40 . In addition, a recent study using MSI has shown hepatocyte heterogeneity in terms of amino acid and lipid composition 69 . Also, using MSI, liver metabolome was shown to change with fasting in a localized pattern, including increased levels of fatty acids and tricarboxylic acid cycle intermediates 70 …”
Section: Spatial Heterogeneity In the Mammalian Livermentioning
confidence: 99%
“… 40 In addition, a recent study using MSI has shown hepatocyte heterogeneity in terms of amino acid and lipid composition. 69 Also, using MSI, liver metabolome was shown to change with fasting in a localized pattern, including increased levels of fatty acids and tricarboxylic acid cycle intermediates. 70 …”
Section: Spatial Heterogeneity In the Mammalian Livermentioning
confidence: 99%
“…In the vast majority of cases, the analyses with SIMS imaging are focused on either poly-or indeed mono-atomic fragment ions. In some cases such fragment ions can be used as a means of identifying specific classes of metabolites, (Rodimova et al, 2021), thereby allowing healthy tissues to be differentiated from neoplastic formations. (Gularyan et al, 2020).…”
Section: Mass Spectrometry Imagingmentioning
confidence: 99%